Are we currently underestimating the risk of scrum-related neck injuries in rugby union front-row players? - Brown, J. C.; Lambert, M. I.; Hendricks, S.; Readhead, C.; Verhagen, E.; Burger, N.; Viljoen, W. (British Journal of Sports Medicine, 2014)
To understand the risk of incurring a particular rugby injury, and to identify risk factors related to this injury, it is necessary to know the injury counts and the time that the players are exposed to the risk of sustaining that injury. The latter poses an interesting debate with respect to the scrum as there are various ways in which the exposure can be expressed. While they are not the only two methods, `exposure` in sports injury epidemiology has often been calculated either by the `Athlete at risk` method or the `Athlete participation` method. The `athlete participation` method is sometimes the only way to calculate injury incidence rates for certain investigations, such as for catastrophic injury risk, in which data are mainly collected retrospectively. However, this method typically underestimates injury rates as the exact time at risk is not quantified. Where match time is recorded, the current consensus statement for the surveillance of injuries in rugby union provides a formula for the calculation of match exposure. This consensus statement, which defines terms and preferred methodology, has significantly advanced the quality of research on injuries associated with rugby union by offering guidelines for a standardised approach, enabling universal comparison of injury risk and risk factors